Accuracy of Inhaler Use in COPD Patients and Factors Affecting It - Indah Kusumawati Susanti; Rani Sauriasari; Anna Rozaliyani; Dodi Sudiana (Jurnal Respirologi Indonesia, 2023)
Background: An inhaler is a type of dosage form used in the treatment of chronic obstructive pulmonary disease (COPD). The inhaler has a unique technique for use; however, the percentage of accuracy in inhaler use is still low. Proper inhaler use is expected to improve quality of life and decrease the occurrence of exacerbations. This study aimed to observe the percentage of accuracy in using inhalers and the factors that influence it.Method: This study was conducted with a cross-sectional design on COPD patients in two different hospitals. Primary data were collected using a questionnaire. The accuracy of inhaler use was assessed using a checklist.Results: The total number of patients in this study was 110, with an average age of 62 years. Patients were given single inhaler therapy, which included Dry Powder Inhalers (DPI) for 34 patients with 70.7% accuracy, Pressurized Metered-Dose Inhalers (pMDI) for 9 persons with 45.74% accuracy, and Soft Mist Inhalers (SMI) for one person with 66.67% accuracy. Furthermore, patients who used a combination of pMDI and DPI inhalers had an accuracy value of 68.53%, while a combination of pMDI and SMI had an accuracy value of 72.72%. The stage with the lowest level of accuracy in the pMDI-type inhaler used alone was exhaling before the inhaler was supplied.Conclusion:  According to the findings, the accuracy of inhaler use in COPD patients is still relatively low. Furthermore, gender is a factor that has a statistically significant relationship with inhaler accuracy.